2018
DOI: 10.1111/micc.12446
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of collaterals in the human gingiva by laser speckle contrast imaging

Abstract: Objective The rate of blood flow between the various areas of the gingiva in resting position and under challenge is unknown. In this study, the LSCI method was used to map spatial and temporal changes in gingival blood flow after transient compression. Methods Horizontal, vertical, and papilla base compressions were applied on the attached gingiva in 21 healthy patients (13 women, 8 men). LSCI was used to determine dynamic changes in regional blood flow during a five‐second occlusion interval and subsequent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
(97 reference statements)
4
17
0
Order By: Relevance
“…The apical direction of spreading vasodilation reaffirms the priority of the plexus of the alveolar mucosa in blood supply to the keratinized gingiva in physiological conditions and during regular flap elevation or wounding . It also concurs with the ascending feature of flow‐mediated vasodilation.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The apical direction of spreading vasodilation reaffirms the priority of the plexus of the alveolar mucosa in blood supply to the keratinized gingiva in physiological conditions and during regular flap elevation or wounding . It also concurs with the ascending feature of flow‐mediated vasodilation.…”
Section: Discussionsupporting
confidence: 64%
“…In some regions, there was a tendency of reduction in GBF at the control site, which may be explained by the slight drop in gingival temperature and in mean arterial blood pressure during the blood flow measurement. A slight drop (marginally significant) in blood pressure was also observed in another LSCI study where the patient was in relaxed position for 30‐40 minutes and no vasoactive drug was applied suggesting that the observed decrease in blood pressure may not due to the systemic effect of Nitromint. The drop is probably caused by the prolonged relaxed position with an open mouth.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, papillary blood flow remained unchanged after the horizontal incision. In a previous study (Fazekas et al, ), compression at the base of the papilla caused a 55% drop in blood flow at the marginal gingiva of the nearby teeth. This suggests that papillary collaterals (intraseptal, lingual) contribute significantly to the blood supply of the marginal gingiva and may readily supply the coronal area after horizontal incision, which explains our unexpected finding.…”
Section: Discussionmentioning
confidence: 82%
“…The relative contribution of these anastomoses to maintaining blood supply in physiological and pathophysiological conditions has been less well researched. In a challenging situation induced by short‐time horizontal compression of the gingival vessels, the compensatory blood comes from the alveolar mucosa (Fazekas et al, ). This apico‐coronal direction was also confirmed in a series of case studies by Mormann (Mormann & Ciancio, ; Mormann, Meier, & Firestone, ), who found that marginal gingival perfusion is sensitive to the horizontal incision.…”
Section: Introductionmentioning
confidence: 99%